2013
DOI: 10.1186/2193-1801-2-532
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interval training intensity on fat oxidation, blood lactate and the rate of perceived exertion in obese men

Abstract: PurposeThe objectives of this study were to examine the effect of 4-week moderate- and high-intensity interval training (MIIT and HIIT) on fat oxidation and the responses of blood lactate (BLa) and rating of perceived exertion (RPE).MethodsTen overweight/obese men (age = 29 ±3.7 years, BMI = 30.7 ±3.4 kg/m2) participated in a cross-over study of 4-week MIIT and HIIT training. The MIIT training sessions consisted of 5-min cycling stages at mechanical workloads 20% above and 20% below 45%VO2peak. The HIIT sessio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
1
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 40 publications
3
39
1
10
Order By: Relevance
“…In this context, we have to note that HIIT group had the greater decrease in the RPE score, which corroborates with the findings of a recent study (Alkahtani et al, 2013). Therefore, we can conclude that the two types of training program reflected a decrease in plasma leptin levels.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In this context, we have to note that HIIT group had the greater decrease in the RPE score, which corroborates with the findings of a recent study (Alkahtani et al, 2013). Therefore, we can conclude that the two types of training program reflected a decrease in plasma leptin levels.…”
Section: Discussionsupporting
confidence: 79%
“…Further, both training modalities enhanced positively the plasma leptin levels which were based on supplementary energy expenditure leading to the body fat mass decrease. As recently demonstrated (Alkahtani et al, 2013), the interval training intensity in the current study (HIIT and MIIT) helped to decrease fasting plasma glucose levels in both groups. This is due to the enhancement of insulin sensitivity (Host et al 1998), shown in the following study by a decrease in HOMA-IR.…”
Section: Discussionmentioning
confidence: 55%
“…Alkahtani et al 5 examined the effect of 4-week MIIT and HIIT on fat oxidation and the responses of blood lactate and rating of perceived exertion in obese men. The MIIT protocol alternated cycling stages (1:1) between 25% and 65% of mechanical workloads, while HIIT combined stages of work (1:1) at 90% with rest.…”
Section: ‘Intensity’ Is Not the Only Difference Between Hiit And Contmentioning
confidence: 99%
“…Both types of exercise have been prescribed to sedentary and obese individuals, and resulted in improved blood pressure (BP), heart rate (HR), body composition, biochemical markers (insulin, glucose, cholesterol, etc. ), and strength [615]. Combination training (i.e., aerobic and resistance training combined) appears to have a greater effect on BP, arterial stiffness, body composition, and V˙O2max than performing either type of exercise independently [13, 14].…”
Section: Introductionmentioning
confidence: 99%